МОЖНИТЕ КРАТКИ ЛИЧНОЗАМЕНСКИ ФОРМИ ПРИ УДВОЈУВАЊЕТО НА ТРИВАЛЕНТНИТЕ ГЛАГОЛИ (Philological Studies, 2019)
In this paper, we are going to present possible short pronouns about direct and indirect objects, used together with trivalent verbs in Macedonian language.